2017
DOI: 10.1111/pbi.12822
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of alternative splicing landscape responsive to drought, heat and their combination in wheat (Triticum aestivum L.)

Abstract: SummaryPlant can acquire tolerance to environmental stresses via transcriptome reprogramming at transcriptional and alternative splicing (AS) levels. However, how AS coordinates with transcriptional regulation to contribute to abiotic stresses responses is still ambiguous. In this study, we performed genome‐wide analyses of AS responses to drought stress (DS), heat stress (HS) and their combination (HD) in wheat seedlings, and further compared them with transcriptional responses. In total, we found 200, 3576 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 57 publications
12
137
0
Order By: Relevance
“…Previous studies have proven that transcriptional regulation and AS regulation are two parallel processes that function independently in the stress response with little overlap between target genes (Li et al ., ; Chang et al ., ; Ding et al ., ; Ling et al ., ; Liu et al ., ). In our analysis, we confirmed that transcriptional and AS regulation also affect distinct gene sets and biological processes, providing further evidence for their independent regulatory roles.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have proven that transcriptional regulation and AS regulation are two parallel processes that function independently in the stress response with little overlap between target genes (Li et al ., ; Chang et al ., ; Ding et al ., ; Ling et al ., ; Liu et al ., ). In our analysis, we confirmed that transcriptional and AS regulation also affect distinct gene sets and biological processes, providing further evidence for their independent regulatory roles.…”
Section: Discussionmentioning
confidence: 97%
“…The HS‐responsive genes with AS regulation were defined based on the following criteria: (i) the highly expressed transcript set (FPKM ≥ 1.0 and all junction sites that were fully supported by Illumina reads) differed between the control and HS‐treated samples; (ii) for the highly expressed transcript (FPKM ≥ 1.0), the transcript expression percentage (transcript expression/the expression sum of all transcripts of the same gene) changed by more than 30% between the control and HS‐treated samples (Liu et al ., ), with supported Illumina read counts ≥5 for both samples, and the supported Illumina reads significantly differed (chi‐squared test, FDR‐corrected P ‐value <0.05) between the two samples.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Abiotic stress‐mediated changes in splicing have recently been confirmed by several RNA‐seq analyses in plants. Whereas transcriptome profiling has highlighted shift in the expression and dominance of certain isoforms of splicing factors and splice variants accompanying stress response (Liu et al, ; Zhang et al, ), the mode of implementation of this regulation is far from clear. Increasing evidence suggest that ABA‐mediated response is mediated by pre‐mRNA splicing (Haak et al, ; Zhan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during the development of seed, endosperm and embryo, the AS isoforms change significantly in maize [39]. In wheat, 251, 6618 and 7541 AS isoform changes were detected in response to drought stress, heat stress and combined stress in 9312 stress-responsive events, respectively [40]. But little is known about the number of AS changes in response to cold acclimation.…”
Section: Discussionmentioning
confidence: 99%